Biochemical Markers of Mitochondrial Dysfunction In Bangladeshi Autistic Children (East West Medical College Journal, 2026)
Background: Autistics spectrum disorder is a generalized term for a group of complex brain disorder. Autistics spectrum disorder can occur due to dysfunction of mitochondria and abnormal brain bioenergetics. Cellular function impairment due to mitochondrial dysfunction may cause cognitive impairment, language deficits and abnormal energy metabolism in autism. Objective: to evaluate biochemical evidence of the mitochondrial dysfunction by measuring blood ammonia, serum lactate, creatinine kinase (CK), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in autistic children. Methods: This case-control study was conducted in the Department of Physiology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from January, 2013 to December, 2013.  For this study a total number of 100 male children with age range 3-8 years were randomly selected, among which 50 were normal children and 50 were diagnosed autistic children. The autistic children were selected from the Parent’s Forum, Directorate Generals of Health Service (DOHS), Mohakhali, Dhaka and normal children were selected from some normal school. Blood ammonia, serum lactate, aspartate aminotransferase (AST), alanine aminotransferase (ALT) and creatinine kinase (CK) level were estimated in all children by standard laboratory method. Independent sample‘t’ test was used for statistical analysis as applicable. P value